THE LIQUID ROCKET FEED-SYSTEM RCX-300H: CENTRIFUGAL PUMP AND IMPULS TURBINE DESIGN - LUTHFY MAHENDRA (NIM: 23115010), FAISHOL
LAPAN as a government agency in space technology research and development, based on the Law of the Republic of Indonesia number 21 of 2013 concerning space, aiming to realize the independence and competitiveness of a nation and state in organizing space, this research intends for humanity. The initial stage of this study focused on the preliminary study of turbine pumps for the RCX-300H engine. This type of engine is chosen because the thrust produced is small, so the need for fuel is also small, where this engine has gone through several burn tests and has been proven to produce thrust. The initial process of designing a turbine pump system in a liquid rocket is by knowing its needs, which is then performed geometry modeling with the help of CAD and CFD (Computational Fluid Dynamics) simulating software which results in graphical performance characteristics of these components. The calculation results show that the amount of head and debit of fuel in the rocket engine system is 9.6∗10−4 𝑚3/𝑠 (𝑚̇=1.44 𝑘𝑔/𝑠) with a head 255 meter for oxidizer, and 4.3 ∗10−4 𝑚3/𝑠 (𝑚̇=0.34 𝑘𝑔/𝑠) with a head 400 meter for kerosene. The simulation results show that for kerosene centrifugal pumps it requires 2,324.9 Watt of shaft power with 63.91% rotor efficiency, oxidizer centrifugal pump requires a shaft power of 7,510.44 Watt with 50.52% rotor efficiency, and an impulse turbine produces a shaft power of 20,448.8 Watt under pressure ratio 1.96 with rotor efficiency 56.4